EKSISTENSI OJEK PANGKALAN DI TENGAH ADANYA OJEK ONLINE (PERSPEKTIF SOSIAL EKONOMI) DI KECAMATAN MARPOYAN KOTA PEKANBARU - Gusmika "; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was carried out at the Kartama Marpoyan Motorcycle Base in Pekanbaru, Riau Province. The purpose of this study was to determine To determine the existence of a base motorcycle taxi in the midst of an online motorcycle taxi in Pekanbaru City and to find out the strategy of base motorcycle taxi competition for online motorcycle taxi transportation in Pekanbaru City. The technique of writing samples is by purposive sampling in determining the informants. Purposive sampling is the determination of informants not based on strata, positions, guidelines, or regions but based on the existence of specific objectives and considerations that are still related to the research problem. The research method used is descriptive qualitative research method that is research that describes the situation of an event. The results of the writing explain that How is the existence of a base motorcycle taxi in Pekanbaru after the existence of an online motorcycle taxi in maintaining its existence and How is the competition strategy for Base Motorcycle in the midst of an Online Motorcycle taxi in the city of Pekanbaru. The existence of the ojek pangkalan now is very worrying besides the loss of consumer loyalty as well as decreasing their income than usual. The online motorcycle taxi turned out to be very influential on the income of the members of the pangkalan ojek at the Kartama base in Marpoyan Pekanbaru. Keywords: Existence, Ojek Pangkalan and Ojek Online